THE ABUNDANCE OF POTENTIALLY TOXIC EPIPHYTIC DINOFLAGELLATES AND NUTRIENTS FROM BALI AND GILI TRAWANGAN, INDONESIA - Skinner, Mark (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2011)
There are strong indicators that the degradation of coral reefs may increase the intensity and frequency of ciguatera fish poisoning (CFP) outbreaks when denuded reef surfaces are colonised by macro algae that are the preferred hosts of toxic dinoflagellates that can cause the disease. Ciguatera field studies have concentrated on the dinoflagellate genus Gambierdiscus, well known to be the producer of ciguatoxin precursors. Moreover the potential of toxins from other dinoflagellate genera such as Prorocentrum and Ostreopsis is less often considered. Whilstit is known that toxic compounds produced by Ostreopsis species include ostreotoxins (OTX) and ostreocins, the potential harmful impacts of Ostreopsis, Prorocentrum and Gambierdiscus species on coral reef organisms (and ecological impacts) are largely unknown. In addition, CFP has historically largely occurred on the oceanic islands of the worldâ??s tropical seas, but has only recently been reported in the major archipelagoes of Indonesia and thePhilippines. In view of their degraded coral reef ecosystems and the potential link between reef health and CFP, this study examined three sites in Bali and Gili Trawangan over one year, to assess the prevalence and distribution of CFP related dinoflagellate species. Beside finding Gambierdiscus, Ostreopsis and Prorocentrum at most sites, water column nitrogen nutrient levels were also found on the average to be 3â??4 times higher than that recommended for a healthy coral reef (0.013mg/L). However the maximum abundance of Prorocentrum, Ostreopsis and Gambierdiscus found were low (103, 2,860 and 28 cells per gram of wet weight of host macroalgae, respectively). A factor thatmay play a part in the potential for toxicity at these sites is the abundance of sea grass (and associated micro flora and fauna) which are often present within and adjacent to coral reef ecosystems across the Indonesian archipelago.